2009
DOI: 10.1074/jbc.m900325200
|View full text |Cite
|
Sign up to set email alerts
|

The Accessory SecA2 System of Mycobacteria Requires ATP Binding and the Canonical SecA1

Abstract: In bacteria, the majority of exported proteins are transported by the general Sec pathway from their site of synthesis in the cytoplasm across the cytoplasmic membrane. The essential SecA ATPase powers this Sec-mediated export. Mycobacteria possess two nonredundant SecA homologs: SecA1 and SecA2. In pathogenic Mycobacterium tuberculosis and the nonpathogenic model mycobacterium Mycobacterium smegmatis, SecA1 is essential for protein export and is the "housekeeping" SecA, whereas SecA2 is an accessory SecA that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
67
10

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 49 publications
5
67
10
Order By: Relevance
“…6); SecA2 was found predominantly in the soluble fraction with only a small amount of protein detected at the membrane, whereas SecA1 was detected only at the membrane. This is in stark contrast to M. smegmatis, where SecA1 was found to be localized equally between the membrane and cytoplasm (31). However, as was observed in M. smegmatis, the dominant-negative K106R mutation in SecA2 switched the localization of the protein entirely to the membrane fraction.…”
Section: Translocation Of Other Cwps Is Affected By Seca1(k106r)contrasting
confidence: 47%
See 4 more Smart Citations
“…6); SecA2 was found predominantly in the soluble fraction with only a small amount of protein detected at the membrane, whereas SecA1 was detected only at the membrane. This is in stark contrast to M. smegmatis, where SecA1 was found to be localized equally between the membrane and cytoplasm (31). However, as was observed in M. smegmatis, the dominant-negative K106R mutation in SecA2 switched the localization of the protein entirely to the membrane fraction.…”
Section: Translocation Of Other Cwps Is Affected By Seca1(k106r)contrasting
confidence: 47%
“…Cellular Distribution of SecA1 and SecA2-It has been previously reported that M. smegmatis SecA1 and SecA2 differ in their subcellular localization; SecA1 was found equally in cytoplasmic and membrane fractions, whereas SecA2 was predominantly cytoplasmic (31). Furthermore, the SecA2(K129R) mutation, analogous to the SecA2(K106R) mutation described in this study, relocalized SecA2 predominantly to the membrane.…”
Section: Translocation Of Other Cwps Is Affected By Seca1(k106r)mentioning
confidence: 79%
See 3 more Smart Citations